PHYSICIANS AND DISRUPTION ON TELEMEDICINE: A SYSTEMATIC LITERATURE REVIEW - Arief Priyo Nugroho; Ardanareswari Ayu Pitaloka (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2023)
Background: Telemedicine has developed rapidly since the COVID-19 pandemic. Telemedicine applications have marked significant transformations in healthcare. Rapid changes in healthcare services inevitably affect health service providers, specifically physicians. Aims: This study examines physicians' responses to a disruptive era in the healthcare industry. Methods: This paper applies a systematic literature review approach to characterize physicians' experiences, challenges, and obstacles in managing disruption in the health service delivery context. A comprehensive literature review was conducted using the Scopus database and borrowing PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. There were 78 articles included in the analysis. Results: This study found that doctors who use telemedicine experience several types of disruption. The studies that examine physicians' experience in health service disruption tend to be dominant in 4 (four) out of 5 (five) disruption types. First, disruption to the current delivery mode. Second, disruption to clinical practice role and responsibility. Third, disruption to clinical practice role and responsibility. Fourth, disruption to the work environment. Meanwhile, the disruption in personal life becomes less elaborated in the telemedicine studies debate. Conclusion: It is essential to pay close attention to the disruptions that have an effect on physicians' personal lives. Personal life is essential because it benefits physicians and directly supports the quality and sustainability of telemedicine services. Keywords: Disruption, Physician, and Telemedicine.